"Way-Centered" versus "Truth-Centered" Epistemologies - Kai Horsthemke (MDPI AG, 2016)
In recent years, a criticism of "indigenous knowledge" has been that this idea makes sense only in terms of acquaintance (or familiarity) type and practical (or skills-type) knowledge (knowledge-how). Understood in terms of theoretical knowledge (or knowledge-that), however, it faces the arguably insurmountable problems of relativism and superstition. The educational implications of this would be that mere beliefs or opinions unanchored by reason(s), such as bald assertions, superstitions, prejudice and bias, should not be included in the curriculum, at least not under the guise of "knowledge". Worthy of inclusion are skills and practical knowledge, as are traditional music, art, dance and folklore (qua folklore). Moreover, anything that meets the essential requirements for knowledge-that could in principle be included. Against this understanding of knowledge, and its educational implications, it has been contended that indigenous knowledge places no special emphasis on "belief", "evidence" or "truth", but that, according to indigenous practitioners, it is rather "the way" that constitutes knowledge, harmonious interaction and appropriate models of conduct. It has been argued, further, that cognitive states are (to be) seen as "maps", as useful and practical action-guides. This is why (so the argument for "polycentric epistemologies" or "polycentric global epistemology" goes) divination, rain-making, rain-discarding, shamanism, sorcery, ceremony, ritual, mysticism, etc., must be acknowledged as ways of knowing (and as educationally valuable) alongside animal husbandry, botany, medicine, mathematics, tool-making, and the like. The present paper investigates whether the "way-based" epistemological response is a plausible reply to the "truth-based" critique of indigenous knowledge (systems).